Kajian Etnobotani Tanaman Asam (Tamarindus indica L.) Di Manatuto Vila Timor-Leste - Pinto, Alice (Berkala Ilmiah Biologi, 2025)
Abstract: Tamarindus indica L. is a type of multifunctional tree, because it has various ethnobotanical benefits. This study aims to determine the sources of tamarind plant, the use of ethnobotany and the source of local community knowledge regarding the ethnobotanical utilization of this plant. The type of this research is a qualitative and the methods used are interview and observation. The research results show that the local community could obtain tamarind from their yards with the highest percentage at 74%. The results of ethnobotanical utilization shows that acid seeds as a food ingredient with the highest IC value of 100%, followed by the use of leaves and fruits as traditional medicine with a value of 98%, leaves shoots, fruit and flowers as kitchen spices with a value of 96%, the use of branches and twigs as firewood with a value of 88%. The sources of this knowledge were obtained from the ancestors with the highest percentage of 98%. Thus, it can be concluded that tamarind plant has multiple functions in ethnobotany, which is a cultural heritage from their ancestors and still preserved at present.